UPAYA PARTISIPASI MASYARAKAT SEBAGAI KEMANDIRIAN EKONOMI DESA MENGHADAPI COVID 19 DESA JUNREJO KECAMATAN JUNREJO KOTA BATU - Roro Merry Chornelia Wulandari; Alfridus Ariyanto Dara Mone (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2022)
The COVID-19 pandemic has caused unplanned social changes as social changes that occur erratically and whose presence is not desired by the community. Village independence efforts and village community participation must be needed and have the initiative to create an economically independent community in the face of a pandemic situation. Covid 19 is to be faced by rural communities. The purpose of this research to find out the efforts of community participation as village economic independence in Covid 19 in Junrejo village, Junrejo district, Batu city and to find out what are the supporting and inhibiting factors in community participation efforts as an effort to achieve village economic independence in Covid 19 in Junrejo Village, Junrejo District, Batu City. This study uses the determination of informants, research instruments, snowball sampling, data collection techniques, and technical data analysis, namely data reduction, data presentation, and conclusion drawing. The results showed that the efforts of the community to ensure the independence of the village faced Covid-19 in the villager of Junrejo, namely: the emancipation of the community has changed for the better, especially when viewed from the point of view of community skills and creativity in the management of flower beds, which made it a source of income, adequate public institutions. Such as providing free internet in the form of village wifi to access information, selling agricultural products online, and village cooperatives to create an improved and better standard of living for the people of Junrejo